The construction of categories in sport: Unfair advantages, equality of opportunity and strict attainability - Camporesi Silvia; Hämäläinen Mika (TAYLOR & FRANCIS LTD, 2025)
On 8 September 2020, the Swiss Federal Supreme Sport dismissed the double appeal by Caster Semenya against the decision of the Court for Arbitration of Sport to uphold the World Athletics regulations restricting testosterone levels in female runners. On 24 February 2021, Semenya appealed to the European Court of Human Rights. This is the most recent episode of an international legal case which was ignited at the 2009 Berlin World Track Championship, when Semenya was 18 years old. Semenya's case has generated an intricate web of questions for classification in sport that are yet to be resolved. In this paper we aim to disentangle them. We proceed as follows: we describe the problem of binary classification related to Semenya's case and introduce the concept of property advantage, and the fair equality of opportunity principle. We compare Semenya's case with Eero Mantyranta's case and fail to identify a way according to which the two cases could justifiably be treated differently. We then discuss three possible ways to organize sport categories based on the combination of Loland's fair equality of opportunity principle and our strict attainability criterion, and outline the implications of each alternative for international sports law regulation. Finally, we summarize and outline the legacy of Semenya for the construction of categories in sport.